Pengaruh Penambahan Vitamin E Komersil pada Pengencer Andromed Terhadap Kualitas Spermatozoa Pre-freezing Sapi Simental di UPT-PIBPS Provinsi Sulawesi Selatan: Effect of Commercial Addition of Vitamin E to Andromed Diluent on Pre-Freezing Spermatozoa Quality of Simmental Cattle - Sartika, Yuni; Paly, Muhammad Basir; Mappanganro, Rasyidah (Anoa: Journal of Animal Husbandry, 2022)
This study aimed to determine the effect of addition of vitamin E commercial in andromed diluent on the pre-freezing spermatozoa quality in simmental cattle. The research method used a completely randomized design (CRD) method with 3 treatments and 5 replications, namely P0 (control), P1 (+ vitamin E 1 mg/ml) and P2 (+ vitamin E 3 mg/ml). Parameters measured were macroscopically (motility, viability and abnormality) at the time of pre-freezing. The results of this study showed a very significant effect (P<0.01) on the motility and viability of spermatozoa in the pre-freezing phase and showed no significant effect (P>0.05) on the abnormality of spermatozoa in the pre-freezing.